Development of relations between Ethiopia and China during Emperor Haile Selassie: a product of timing or the leadership? - Mesafint Tarekegn Yalew (Cogent Social Sciences)
This article delves into the development of the diplomatic relationship between Ethiopia and China during Emperor Haile Selassie. The author utilizes a combination of primary and secondary sources. The primary sources were collected from various institutions and offices such as the Institute of Ethiopian Studies (IES), the Ministry of Foreign Affairs of Ethiopia, and periodicals that included memoirs, speeches, and correspondence exchanges. Secondary sources were gathered from both published and unpublished materials. The study focuses on defining the evolution of diplomatic relations between the two countries throughout the 1970s. This particular period witnessed China’s diplomatic triumph on the global stage, prompting Ethiopia to seek an alternative ally to the West. This development occurred when the United States attempted to exploit this advantage by re-establishing its ties with the People’s Republic of China (PRC). The findings of this study assert that after Ethiopia set aside all obstacles and endeavored to establish diplomatic ties with China on December 1, 1970, it became evident that the country was adopting a hedging strategy to distance itself from its long ally, the US. Following Haile Selassie’s visit to Beijing, Ethiopia and China signed a joint communiqué on economic and technical cooperation. Consequently, the study concludes that the development of diplomatic relations between the two countries coincided with the gradual decline of the US’s influence in Ethiopia.